Cultural Patterns in Zaid Al-Shahid’s Novel "Sabt Ya Thulatha - Assist. Lect . Laila , Abdul-Amir Layem (Basra studies journal, 2025)
This study explores the cultural patterns in Zaid Al-Shaheed’s novel 'Sabt Ya Thulatha' . The author employs diverse narrative techniques—such as flashback, stream of consciousness, and linguistic as well as semantic shifts—to depict events with great precision. The title underscores the centrality of time: Sabt, associated with pessimism due to its relation to Judaism, and Thulatha, marking the tragic bombing of the pedestrian bridge in Samawah, which left indelible scars in the city’s collective memory. The narrative intertwines this catastrophe with the personal tragedy of Najat, whose rape symbolizes the violation of the Iraqi people’s rights across history and reflects the disintegration of social and familial bonds. Through this, Al-Shaheed succeeds in evoking the reader’s sympathy and presenting the novel as a living testimony to Iraq’s suffering under oppression and injustice Sources.